Pengaruh Ekstrak Etanol Daun Binahong (Anredera Cordifolia (Ten.) Steenis Terhadap Ph Dan Tukak Lambung Pada Tikus Putih Betina - Helmi Arifin; Rosa Julia Wijaya; Zet Rizal (STIFARM Padang, 2014)
The effect of binahong (Anredera cordifolia (Ten.) Stennisleaves extract ethanol on pH and gastric ulcers in female rats were induced by 1 ml/200 gram body weight by oral admistration. The parameter taken to asses antiulcer activity were change of gastric acid pH and ulcer index to normal condition. The result indicated that the binahong leaves extract at doses of 30 mg, 100 mg and 300 mg/Kg BB body weight significantly decreased the ulcer index with curative ratio were 38.62 %, 52.41 % and 57.01 % (for one daily of extracts for two days), 60.84 %, 78.74 % and 82.32 % (for one daily of extracts for four days) and 79.91 %, 93.86 % and 95.98 % (for one daily of extracts for two days) with respect to control group. The extracts at 30 mg, 10 mg and 300 mg/Kg BB body weigth also significanthy decreased the gastric acid pH to its normal value (P<0.05).